A Semi-Automatic Approach Based on the Method of Manufactured Solutions to Assess the Convergence Order in OpenFOAM. (2022) - Ramoa, Bruno; Costa, Ricardo; Chinesta, Francisco; Nóbrega, J. Miguel
No abstract available